Growth Differentiation Factor 15 Protects SH-SY5Y Cells From Rotenone-Induced Toxicity by Suppressing Mitochondrial Apoptosis - Li, Peizheng; Lv, Hongbo; Zhang, Bohan; Duan, Ruonan; Zhang, Xiufang; Lin, Pengfei; Song, Chengyuan; Liu, Yiming (Frontiers in Aging Neuroscience, 2022)
Objective Parkinson’s disease (PD) is the second most common neurodegenerative disorder worldwide. Mitochondrial dysfunction is suspected as one of the pathogenic mechanisms of PD. Growth/differentiation Factor-15 (GDF15) has been reported to affect mitochondrial function in PD. However, the relationship between mitochondrial function and GDF15 induction has not been explained well. Hence, we aimed to reveal the effect of GDF15 induction on SH-SY5Y cells with rotenone toxicity, a cell model of PD. Methods SH-SY5Y cells were exposed to 1 μM rotenone as a PD model. Cells were transfected with a GDF15-overexpression plasmid and empty vector. We then analyzed the expression level of GDF15, BCL-2/BAX, P53, PGC1-α, α-syn, and TH in GDF15-overexpressing cells by western blotting, enzyme-linked immunosorbent assay, and quantitative real-time polymerase chain reaction. The cytotoxicity of rotenone was measured by CCK-8 assays. Cell apoptosis was detected by flow cytometric and TUNEL assays. The effect of GDF15 on oxidative stress and mitochondrial function was revealed using DCFH-DA, mito-SOX, and JC-10 assays and a Seahorse XF Cell Mito Stress Test. Results GDF15 protected rotenone-treated SH-SY5Y cells from toxicity by preserving mitochondrial function and decreasing apoptosis, during which GDF15 might function by influencing PGC1α through the regulation of p53. In addition, GDF15 overexpression could improve Akt and mTOR phosphorylation, leading to PI3K/Akt/mTOR pathway activation. However, these protective effects were eliminated when cells were treated with the PI3K/Akt specific inhibitor LY294002. Conclusion Our findings suggest that GDF15 can protect mitochondrial function and inhibit apoptosis in SH-SY5Y cells after exposure to rotenone by upregulating PGC1α via p53. These properties might comprise its anti-apoptotic effects, mediated by the PI3K/Akt/mTOR signaling pathway.